Can Chinese patients restore normal knee function 1 year after total knee arthroplasty? - Guo, YiShun; Wu, HaoDong; Chang, XiaoFeng; Bao, HuanLi; Ma, JianBing; Xu, Chao; Yao, ShuXin (Frontiers in Medicine, 2025)
ObjectiveTo develop a culturally adapted assessment tool for evaluating one-year postoperative knee function in Chinese patients after total knee arthroplasty (TKA), and to establish foundations for localized evaluation protocols and early postoperative interventions.MethodsThis cross-sectional study systematically reviewed knee function assessment items for post-TKA patients. Based on expert and patient focus group discussions, a set of evaluation items was established, followed by designing a self-administered questionnaire assessing importance, frequency, and difficulty. From February to December 2024, TKA patients at 1 year post-surgery and age-matched healthy controls were recruited at Honghui Hospital, Xi’an, China. High-frequency activities were identified and compared between groups.ResultsA total of 39 culturally relevant knee function items were developed through expert and patient consensus. The study included 713 TKA patients and 675 age-matched healthy controls, and 14 high-frequency activities were identified based on importance ratings. No significant functional differences were observed between TKA patients and controls in individuals under 65 years. In the 65–75-year group, only females showed decreased performance in picking up items from the ground (p < 0.001). Among participants older than 75 years, males showed significant deficits in putting on and taking off shoes and socks (p = 0.008), squatting (p < 0.001), picking up items from the ground (p = 0.009), and carrying heavy objects with one hand (p < 0.001), while females demonstrated reduced ability in bathing and wiping (p < 0.001), picking up items from the ground (p < 0.001), and squatting (p = 0.048).ConclusionMost patients regain daily function 1 year after TKA, but limitations persisted in older patients. The 14 culturally relevant activities identified provide a practical basis for a localized assessment. Future work will involve longitudinal validation and clinical integration to support individualized postoperative rehabilitation.